Low Dose Oxybutynin in Childhood Nocturnal Enuresis - Naseri, Mitra (Journal of Pediatric Nephrology, 2014)
Introduction: To evaluate the response to low dose oxybutynin in children with nocturnal enuresis. Materials and Methods: Forty-one neurologically normal enuretic children who were visited in our nephrology clinic in a 3-year period (2007-2009) received low dose oxybutynin (2.5-10 mg/day depending on the weight) to define response to the drug in one and 3- month periods. No, partial, and full response were defined as 0-49%, 50-89% and ≥90% decrease in bed wetting, respectively. Results: In the first month of treatment, full, partial, and no response were reported in 3 (7.3%), 14 (34.1%), and 24 (58.6%) patients, respectively. In the non-responder patients, 6 (25%) and 5 (20.8 %) patients showed full and partial response in the 3-month period whereas 13 (54.2%) had no response. The side effects of the drug were reported in 5 (12.2%) patients. Children with non-mono symptomatic nocturnal enuresis (NMNE) showed a better response to the drug than those with mono symptomatic nocturnal enuresis (MNE) (75% versus 25%). There was no significant differences in age, gender, family history of enuresis, and the presence or absence of daytime urinary or bowel symptoms between responder and non-responder groups (P>0.05 for all). Conclusions: In this clinical report study, there was 68.3% treatment benefit and 12% risk (side effects of the drug) with low dose oxybutynin. Therefore, it may have a role in treating nocturnal enuresis, especially in patients with NMNE who experience adverse effects of standard treatment (Higher doses of the drug). Keywords: Nocturnal Enuresis; Child; Oxybutynin; Risks and Benefits; Adverse effects.